ANALISIS KESESUAIAN MODEL PENGEMBANGAN SILVOFISHERY KAWASAN MANGROVE DI LANTEBUNG - Ahmad Sajjad; Jayadi Jayadi; Asbar Asbar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Silvofishery (silvocrabs) is a traditional technology aquaculture system that combines fishery business (crab cultivation) with mangrove planting. This study aims to: (1) analyze the feasibility of mangrove land for silvofishery activities, especially in crabs in terms of physical, chemical and biological aspects of the Lantebung mangrove area. (2) analyze silvofishery models (forms) for crabs that can be applied and are in accordance with the Lantebung Mangrove Area. The study was carried out by direct observation methods in the field by taking data on physical, chemical, and biological parameters using direct measurement methods and referring to several other literature. Based on the results of the analysis of the 3 stations observed, station 1 and station 2 are classified as quite feasible while station 3 is classified as very feasible to support silvocrabs development activities. So that the cultivation of silvocrabs is feasible to be developed in the Lantebung Mangrove Area precisely on.